Building a market economy through WTO-inspired reform of state-owned enterprises in China - ZHOU, Weihuan (Institutional Knowledge at Singapore Management University, 2019)
This paper responds to the widespread view that existing WTO rules are insufficient in dealing with China’s state capitalism, which has been further emboldened by its latest rounds of state-owned enterprise (“SOE”) reforms. Through a careful review of WTO agreements and jurisprudence, the paper argues that, we do not necessarily need new rules, because the unique challenges created by China’s state capitalism can be sufficiently dealt with by the WTO’s existing rules on subsidies coupled with the China-specific obligations. Thus, a more realistic approach would be to push China back to the path of market-oriented reforms through WTO litigation based on existing rules, rather than trying to negotiate new rules.